2021
DOI: 10.1038/s41598-021-97640-6
|View full text |Cite
|
Sign up to set email alerts
|

A MATLAB-based program for three-dimensional quantitative analysis of micronuclei reveals that neuroinflammation induces micronuclei formation in the brain

Abstract: The micronucleus is known to be a biomarker for genomic instability, which is a hallmark of tumors and aging. Normally, micronuclei are produced by segregation errors and mechanical stresses arising from dividing or migrating cells, leading to activation of the innate immune response pathway. Although micronuclei often emerge in damaged tissues, the quantitative procedure for analyzing micronuclei accurately has been problematic. Here, we introduce a novel MATLAB-based program for quantifying micronuclei (CAMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Neurons in the cerebral cortex are generated from NPCs in the ventricular and subventricular zone during the embryonic period and migrate to the brain surface. Previously, we observed that MNs exist in the brain of 2-month-old mice 39 . To examine whether MNs also appear in the developing brain, we analyzed the prenatal brain on embryonic day (E) 18.5.…”
Section: Neuronal Micronuclei Are Generated From Migrating Neuronsmentioning
confidence: 86%
See 1 more Smart Citation
“…Neurons in the cerebral cortex are generated from NPCs in the ventricular and subventricular zone during the embryonic period and migrate to the brain surface. Previously, we observed that MNs exist in the brain of 2-month-old mice 39 . To examine whether MNs also appear in the developing brain, we analyzed the prenatal brain on embryonic day (E) 18.5.…”
Section: Neuronal Micronuclei Are Generated From Migrating Neuronsmentioning
confidence: 86%
“…FIJI ImageJ software (NIH) and ZEN (Carl Zeiss) are used for converting each Z-stack image (interval; 1 μm per image, a total thickness of images staining with MAP2; 10 to 15 μm, a total thickness of images staining with Iba1; 30 to 50 μm) to a single TIFF file. The data were imported into the MATLAB-based program CAMDi for quantifying MNs 39 . Briefly, the rate of overlap area of the nucleus is defined as 0.5.…”
Section: Micronuclei Analysismentioning
confidence: 99%
“…Although bone marrow is widely used, because it can be easily obtained, whether it is a proxy for many other tissue types for MN assessment is poorly understood. A recently developed tool, called MATLAB‐based program for quantifying MN, would provide opportunity to quantitatively and accurately analyze MN in brain tissues of AD mice models (Yano et al., 2021 ). Interestingly, a recent study developed a fluorescence probe that is able to specifically target MN (Ding et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of the task is further exacerbated by the unavailability of a standard protocol leading to inter-observer variability while counting. Additionally, density of nuclei in each image and resulting crowding makes it challenging to confidently separate and accurately assign MN events to nuclei for both humans and automated methods 26 . Thus, improved methods for automated CIN quantification are necessary to increase speed, accuracy and robustness of CIN-related research.…”
Section: Mainmentioning
confidence: 99%
“…Here, we present micronuclAI, a novel deep-learning-based pipeline for assessment of CIN through automated quantification of MN from nuclei-stained images. micronuclAI distinguishes itself over previous methods [26][27][28][29][30][31][32] as it 1) can quantify for both MN and NBUDs, 2) requires only nuclear staining, 3) is able to work with 10x to 100x image objectives, 4) can work with any segmentation mask, and most importantly 5) is extensively evaluated in multiple cell lines and thus, ready for use by the community (Fig. 1 and Table 1).…”
Section: Mainmentioning
confidence: 99%